International Portfolio Investment Flows - Brennan, Michael J.; Cao, H. Henry (Journal of Finance, 1997)
This article develops a model of international equity portfolio investment flows based on differences in informational endowments between foreign and domestic investors. It is shown that when domestic investors possess a cumulative information advantage over foreign investors about their domestic market, investors tend to purchase foreign assets in periods when the return on foreign assets is high and to sell when the return is low. The implications of the model are tested using data on United States (U.S.) equity portfolio flows.